Comparative sequence analysis reveals extensive microcolinearity in the lateral suppressor regions of the tomato, Arabidopsis, and capsella genomes - Roßberg, Mathias; Theres, Klaus; Acarkan, Adile; Herrero, Rubén; Schmitt, Thomas; Schumacher, Karin; Schmitz, Gregor; Schmidt, Renate (The plant cell, 2001)
A 57-kb region of tomato chromosome 7 harboring five different genes was compared with the sequence of the Arabidopsis genome to search for microsynteny between the genomes of these two species. For all five genes, homologous sequences could be identified in a 30-kb region located on Arabidopsis chromosome 1. Only two inversion events distinguish the arrangement of the five genes in tomato from that in Arabidopsis. Inversions were not detected when the arrangement of the five Arabidopsis genes was compared with the arrangement in the orthologous region of Capsella, a plant closely related to Arabidopsis. These results provide evidence for microcolinearity between closely and distantly related dicotyledonous species. The degree of microcolinearity found can be exploited to localize orthologous genes in Arabidopsis and tomato in an unambiguous way.